Fixed bed adsorption of CO2, CH4, and N2 and their mixtures in potassium-exchanged binder-free beads of Y zeolite - Aly, Ezzeldin (2021)
The adsorption of carbon dioxide (CO2), methane (CH4), and nitrogen (N2) has been studied on potassium-exchanged (95%) binder-free beads of Y zeolite through single, binary, and ternary fixed bed breakthrough experiments, covering the temperature range between 313 and 423 K and a pressure of up to 350 kPa. At 313 K and 350 kPa, the single-component data obtained showed that the amounts adsorbed of CO2, CH4, and N2 are around 6.42, 1.45, and 0.671 mol kg-1, respectively. The binary experiments CO2/N2 carried out under typical post-combustion conditions show a selectivity of CO2 over N2 around 104. The ternary experiments resulted in the selectivities of CO2 over CH4 and N2 around 19 and 45, respectively. The adsorption equilibrium data have been modeled by the dual-site Langmuir model, and the breakthrough experiments were numerically simulated with a suitable dynamic fixed bed adsorption model. The model predicts with good accuracy the systematic behavior of all breakthrough experiments. The results shown in the present work prove that the potassium-exchanged binder-free beads of Y zeolite enhance the amount adsorbed of CO2 at low partial pressure over other alkali metal-exchanged faujasites and efficiently separate it from binary (CO2/N2) and ternary (CO2/CH4/N2) mixtures by fixed bed adsorption.